Effect of Think Pair and Share (TPS) Learning Model on the Ability to Express Opinions of Grade IV Students of SDN 113 Pekanbaru - Sulistiyaningsih, Wahyu; Lingga, Leny Julia (Jurnal Kiprah Pendidikan, 2025)
This study aims to determine the effect of the Think Pair and Share (TPS) learning model on students’ ability to express opinions. The research was conducted at SDN 113 Pekanbaru during the even semester of 2025 using an experimental design with a quantitative approach. The population consisted of all fourth-grade students, and the sample was selected randomly, comprising class IVA (control group, 27 students) and class IVB (experimental group, 25 students). The independent variable was the TPS model, while the dependent variable was the ability to express opinions.The results showed that the TPS model had a significant effect on students' ability to express their thoughts. The experimental class achieved a higher average score (80.80) compared to the control class (55.74). Hypothesis testing showed a significance value of 0.000 < 0.05 and a t-value of 9.343 > t-table 1.647, indicating that Hₐ was accepted and H₀ rejected. Therefore, the implementation of the TPS model had a significant impact.